2022
DOI: 10.1016/j.jviromet.2021.114341
|View full text |Cite
|
Sign up to set email alerts
|

An easy pipeline for one-step purification of SARS-CoV-2 nucleocapsid protein from insect cell suspension culture

Abstract: The COVID-19 pandemic has demanded a range of biotechnological products for detection of SARS-CoV-2 variants and evaluation of human seroconversion after infection or vaccination. In this work, we describe an easy pipeline for expression of SARS-CoV-2 nucleocapsid (N) protein in insect cells followed by its purification via affinity chromatography. The N gene was cloned into the genome of Autographa californica multiple nucleopolyhedrovirus (AcMNPV) via transpositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Thus, it would be very interesting to test whether SARS-CoV-2 ORF3a is included in virion. One of the well-accepted methods to test this possibility is to subject purified SARS-CoV-2 viral particles to chromatography, by which it can precisely detect whether ORF3a protein is associated with virion ( Shen et al, 2005 ; de Camargo et al, 2022 ). Other confirmed or possible roles of SARS-CoV-2 ORF3a in the SARS-CoV-2 viral life cycle are illustrated in Figure 2 .…”
Section: Roles Of Sars-cov-2 Orf3a In Viral Life Cyclementioning
confidence: 99%
“…Thus, it would be very interesting to test whether SARS-CoV-2 ORF3a is included in virion. One of the well-accepted methods to test this possibility is to subject purified SARS-CoV-2 viral particles to chromatography, by which it can precisely detect whether ORF3a protein is associated with virion ( Shen et al, 2005 ; de Camargo et al, 2022 ). Other confirmed or possible roles of SARS-CoV-2 ORF3a in the SARS-CoV-2 viral life cycle are illustrated in Figure 2 .…”
Section: Roles Of Sars-cov-2 Orf3a In Viral Life Cyclementioning
confidence: 99%
“…The efficient lactosebased autoinduction method reported in this study is an easy-to-adapt method that does not require continuous monitoring of the culture density for the addition of inducers such as IPTG. Other groups have reported the production of recombinant SARS-CoV-2 nucleocapsid protein in different hosts such as E. coli, insects, and mammalian cells [17,[22][23][24][25][26][27]. Li et al reported the purification of nucleocapsid protein from E. coli after refolding of inclusion bodies with a yield of approximately 50 mg/liter fermentation broth [22].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, a SARS-CoV-2 nucleocapsid protein was produced in BEV using a suspension culture of insect cells [ 36 ]. A total of 1 mg of protein was purified from 50 mg of crude protein.…”
Section: Application Of Baculovirus Expression Vector System (Bev) Fo...mentioning
confidence: 99%